2020
DOI: 10.1016/j.jcv.2020.104474
|View full text |Cite
|
Sign up to set email alerts
|

Validation and verification of the Abbott RealTime SARS-CoV-2 assay analytical and clinical performance

Abstract: Highlights The expected 100 copies/mL LOD reported in the EUA Abbott RealTi m e SARS-CoV-2 assay product insert was exceeded. All clinical samples positive for 24 non‒SARS-CoV-2 respiratory viruses were SARS-CoV-2 negative on the RealTi m e assay. The assay had high sensitivity (93%) and specificity (100%) for detecting SARS-CoV-2 in clinical samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 4 publications
2
37
0
Order By: Relevance
“… 33 , 34 , 35 Two studies evaluated Abbott RealTime with rSN or rPPA of 93% to 100%, and rSP or rNPA of 92.4% to 100%. 34 , 36 Three studies evaluated Cepheid Xpert Xpress, with rPPA 96.1% to 100%, rNPA 74.3% to 100%, rOA 96.1% to 100%, and Cohen's Kappa of 0.92. 37 , 38 , 39 Two studies evaluated Diasorin Simplexa with rSN or rPPA of 96% to 100%, and rSN of 100%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 , 34 , 35 Two studies evaluated Abbott RealTime with rSN or rPPA of 93% to 100%, and rSP or rNPA of 92.4% to 100%. 34 , 36 Three studies evaluated Cepheid Xpert Xpress, with rPPA 96.1% to 100%, rNPA 74.3% to 100%, rOA 96.1% to 100%, and Cohen's Kappa of 0.92. 37 , 38 , 39 Two studies evaluated Diasorin Simplexa with rSN or rPPA of 96% to 100%, and rSN of 100%.…”
Section: Resultsmentioning
confidence: 99%
“…With regards to quality evaluation (Supplementary Table 3), most studies did not report method of sample collection/patient recruitment, 33 , 35 , 37 , 41 , 42 , 43 , 44 , 45 , 46 , 47 and four studies conducted a convenience selection of samples, including enrichment for positive samples. 34 , 35 , 36 , 39 Eight studies conducted test performance calculations on sample numbers instead of patient numbers. 33 , 35 , 36 , 38 , 39 , 42 , 43 , 44 Four studies conducted calculation of test performance characteristics with indeterminate or inconclusive results as “positive,” 35 , 38 , 39 , 42 and the management of indeterminate/inconclusive as well as invalid results went unreported in an additional three studies.…”
Section: Resultsmentioning
confidence: 99%
“…According to the package insert, the clinical performance evaluation study showed both 100% positive (95% CI 94, 100) and negative (95% CI 88.8, 100) percent agreement. In a subsequent study, the sensibility and specificity of this assay were found to be 93% and 100%, respectively [12].…”
Section: Sars-cov-2 Testingmentioning
confidence: 86%
“…In Morocco, the rapid test trademark used showed in foreign studies a better sensitivity after 14 days from the onset of symptoms and raised some concerns about its usefulness for COVID-19 confirmation [8]. Controversially, the molecular test of the same trademark was reported as highly accurate in the USA [9]. More information about PoC assays accuracy for Detection SARS-CoV-2 become available, and none of the published studies considers the non-ELISA PoC ones as adapted for detection of suspected patients either symptomatic or asymptomatic, due to the high risk of false negatives especially during the beginning days from the onset [10][11][12][13][14][15][16].…”
Section: Point Of Care (Poc) Serology Tests and Vaccination As Prmentioning
confidence: 99%